Розробка рекомендаційної системи з використанням алгоритмів нечіткої логіки - Гребенюк, М. О. (ХНУРЕ, 2024)
This work is devoted to exploring the implementation of a hybrid fuzzy user model and a corresponding fuzzy distance function to enhance recommendation systems. Utilizing the renowned MovieLens dataset, which comprises user ratings and demographic data for movies, the study delves into data collection, analysis, and the formulation of user models. By integrating fuzzy logic into both the user model and distance calculation, the proposed algorithm offers a promising approach for enhancing recommendation accuracy across diverse application domains.
Keywords: рекомендаційна система; алгоритм нечіткої логіки